CLINICAL CHARACTERISTICS OF LACUNAR ISCHEMIC STROKE PATIENTS - Anindyta Murfia Khairunnisa; Lisda Amalia; Eppy Buchori Aristiady; Harry Galuh Nugraha; Asep Nugraha Hermawan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Background: Stroke is the leading causes of death and disability in the world. Ischemic stroke covered 85% of stroke types. Based on the subtypes of ischemic stroke, lacunar ischemic stroke encompassed 20% of them. Knowing the characteristics help physicians to diagnose patients clinically and offer management to treat risk factors. Objective: This study aimed to know the characteristics of lacunar ischemic stroke based on patients risk factors, ischemic location on CT-scan, clinical syndrome, and NIHSS score. Methods: Using retrospective analytical study with cross sectional approach, medical record data from 2019-2022 were collected from RSUP DR. Hasan Sadikin Bandung. Results: From 60 patients, 35% (21) are 55-64 years old. Both sexes are equally distributed. 50 patients (83.3%) have multiple risk factors. Out of 60 patients, 57 (95%) have hypertension, 8 (13.3%) have diabetes mellitus, 44 (73.3%) have dyslipidemia, 6 (10%) have hyperuricemia, and 14 (23.3%) smoke. On admission, out of 60 patients, 34 (56.7%) have mild stroke, 23 (38.3%) have moderate stroke, 2 (3.3%) have moderate to severe stroke, and 1 (1.7%) has severe stroke. 44 (73.3%) out of 60 patients have pure motor hemiparesis. 41 (68.3%) out of 60 patients have basal ganglia ischemic. Conclusion: Lacunar ischemic stroke patients were equally distributed in sex with peak incidence occur between 55-64 years old. Most patients have multiple risk factors, basal ganglia lesion, pure motor hemiparesis, and history of hypertension, dyslipidemia, and smoking. On admission, most patients have mild stroke, followed by moderate stroke.